Equity, Diversity, and Inclusion on Canadian Universities: Where do international students fit in? - Buckner, Elizabeth; Chan, Elic; Kim, Eun (Comparative and International Education / Éducation comparée et internationale)

(untitled) (University of Western Ontario, 2022)
Internationalization and equity, diversity, and inclusion (EDI) are both strategic priorities at Canadian universities. However, they are underpinned by different emphases and rationales, and their goals and associated activities may be contradictory at times. To explore how the discourses and activities associated with these two projects align or conflict, this article examines how international students are, or are not, included in EDI projects at two of Canada’s largest English-speaking universities: the University of Toronto and the University of British Columbia. Our findings show that the discourses and activities associated with EDI and with international student recruitment have largely operated within organizational and discursive silos, representing a classic case of decoupling in the organizational studies literature. To move forward, we argue that definitions and initiatives related to EDI need to consider how institutions can include international students not only within their commitments to diversity, but also to equity.